Fundamental livestock parturition - Alejandro, Aaron; Benson, David; Davis, G. W.; Hoes, Jay Alan; Maddox, Bill; Creative Educational Video, Inc. (Lubbock, Texas : Creative Educational Video, 1997)
The goal of this video is an introduction to the parturition of three domesticated animals and the objective is to enable the student to learn step by step signs and management practices of parturition in cattle, sheep, and swine. This covers the fundamentals of mating, gestation, lambing, farrowing, and calving.
Fakulti Perubatan Veterinar.
Keywords: Cattle -- Parturition; Livestock -- Reproduction; Sheep -- Parturition; Swine -- Parturition